(untitled) (Geospatial Health, 2009)
Beekeeping in Brazil is growing but also associated with an increase in the number of human and animal accidents involved. In particular, bees of the Apis mellifera species (Africanized bees) are known for their aggressive behaviour and frequent swarming activity due to their poor adaptation to the human environment. This study analyzed the spatial distribution of occurrences of migratory swarms of A. mellifera and recorded apicultural accidents in the city of Salvador, Bahia, Brazil. The association of demographic and climatic variations on places where the swarms occurred was also evaluated. The study is based on data collected within the frame of the SOS Bees, a project initiated for the protection of the environment and enforced by a special unit of the military police in Bahia. In the 3-year period from 2000 to 2003, 590 swarms were registered in 75 of the 98 zones of information of Salvador. Three cluster areas, representing 25.4% of all events, were identified. In that period, 316 apicultural accidents were registered involving humans and one involving dogs. The seasonal rise of the monthly average temperature showed an association with the increase of the number of swarming events.